1994
DOI: 10.1007/bf00043867
|View full text |Cite
|
Sign up to set email alerts
|

Modification of carbonic anhydrase activity by antisense and over-expression constructs in transgenic tobacco

Abstract: The activity and location of carbonic anhydrase has been modified by transformation of tobacco with antisense and over-expression constructs. Antisense expression resulted in the inhibition of up to 99% of carbonic anhydrase activity but had no significant impact on net CO2 assimilation. Stomatal conductance and susceptibility to water stress appeared to increase in response to the decline in carbonic anhydrase activity. An over-expression construct designed to increase cytosolic carbonic anhydrase abundance r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(40 citation statements)
references
References 17 publications
2
38
0
Order By: Relevance
“…Modeling studies (Cowan, 1986), a decrease in carbon isotope discrimination in transgenic tobacco (Nicotiana tabacum) plants with severely reduced CA activity (Price et al, 1994;Williams et al, 1996), the coelution of b-CA and Rubisco, along with other enzymes of the photosynthetic carbon reduction cycle, in multienzyme complexes (Jebanathirajah and Coleman, 1998), and the colocalization of b-CA and Rubisco in sections of pea chloroplasts (Anderson and Carol, 2004) are consistent with this hypothesis. The lack of a significant effect on CO 2 assimilation when CA activity was reduced using antisense and gene knockout technologies (Majeau et al, 1994;Price et al, 1994;Ferreira et al, 2008), except during early seedling development in Arabidopsis (Ferreira et al, 2008), however, argues against chloroplastic b-CA in C 3 plants having a major role in photosynthesis.…”
Section: Plastidial Ca Isoforms Have Multiple Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Modeling studies (Cowan, 1986), a decrease in carbon isotope discrimination in transgenic tobacco (Nicotiana tabacum) plants with severely reduced CA activity (Price et al, 1994;Williams et al, 1996), the coelution of b-CA and Rubisco, along with other enzymes of the photosynthetic carbon reduction cycle, in multienzyme complexes (Jebanathirajah and Coleman, 1998), and the colocalization of b-CA and Rubisco in sections of pea chloroplasts (Anderson and Carol, 2004) are consistent with this hypothesis. The lack of a significant effect on CO 2 assimilation when CA activity was reduced using antisense and gene knockout technologies (Majeau et al, 1994;Price et al, 1994;Ferreira et al, 2008), except during early seedling development in Arabidopsis (Ferreira et al, 2008), however, argues against chloroplastic b-CA in C 3 plants having a major role in photosynthesis.…”
Section: Plastidial Ca Isoforms Have Multiple Functionsmentioning
confidence: 99%
“…It has been suggested that C 3 chloroplastic b-CAs are responsible for maintaining adequate levels of CO 2 for Rubisco by facilitating the diffusion of CO 2 across the chloroplast envelope or through the rapid dehydration of bicarbonate to CO 2 (Reed and Graham, 1981;Cowan, 1986;Price et al, 1994). However, CA antisense and gene knockout studies have shown no significant impairment in CO 2 assimilation in mature plant leaves (Majeau et al, 1994;Price et al, 1994;Williams et al, 1996;Ferreira et al, 2008). Other work has suggested that chloroplastic b-CAs may have nonphotosynthetic roles, appearing to be involved in lipid biosynthesis (Hoang and Chapman, 2002) and disease resistance (Slaymaker et al, 2002;Restrepo et al, 2005;Wang et al, 2009) in C 3 plants.…”
mentioning
confidence: 99%
“…The leaves of tobacco plants containing the antisense b-CA gene have only about 10% or less of the CA activity of wild-type plants. One group reported no deleterious effects of the reduction in CA activity ) and a second group reported that the antisense plants compensated for the decrease in CA with an increase in stomatal conductance leading to an increase in water loss (Majeau, Arnoldo & Coleman 1994). The reasons for the increased drought sensitivity are unclear although it is possible that a reduction in photosynthesis due to a decrease in the rate of delivery of CO 2 to Rubisco caused the leaf stomata to remain open.…”
Section: Carbonic Anhydrases In Plants and Algae 149mentioning
confidence: 99%
“…To date antisense constructs developed in tobacco suggest that the chloroplast stroma b-CA in higher plants plays a minimal role, if any, in photosynthesis (Majeau et al 1994;Price et al 1994). Observations using Arabidopsis suggest that this question needs to be investigated further.…”
Section: Chloroplast Stroma B-camentioning
confidence: 99%
“…Thus, the predicted catalytic Zn content could be more than that of the intracellular Zn in H. banksii. However, the estimated catalytic Zn content could exceed the actual requirement even in C 3 land plants, based on problems with inducing phenotypic effects attributable to lowered CA activity as a result of Zn deficiency and of down-regulation of CA by genetic manipulation in C 3 land plants (Ohki 1976;Majeau et al 1994;Price et al 1994). …”
Section: Roles Of and Quantitative Requirements For Zn In The Phaeomentioning
confidence: 99%